2020
DOI: 10.3892/mmr.2020.11190
|View full text |Cite
|
Sign up to set email alerts
|

miR‑320‑3p is involved in morphine pre‑conditioning to protect rat cardiomyocytes from ischemia/reperfusion injury through targeting Akt3

Abstract: Morphine pre-conditioning (MPc) can significantly reduce myocardial ischemic injury and inhibit cardiomyocyte apoptosis, but the underlying mechanism still remains unclear. The aim of the present study was to investigate the protective mechanism of MPc in myocardial hypoxia/reoxygenation (H/r) injury at the microrna (mir) level. H9c2 cells were used as a model of H/r and subjected to morphine pre-treatment. The protective effects of MPc on H/r injury in cardiomyocytes were evaluated using MTT and colorimetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Previous research on miR-320-3p has focused on pulmonary hypertension, ischaemia/reperfusion injury and muscle wasting in obesity. [10][11][12] In this study, the death group showed greatly higher the levels of serum miR-320-3p, NGAL, KIM-1 and the APACHE II mark than the survival group, suggesting that the levels of serum miR-320-3p, NGAL and KIM-1 are related to the severity of sepsis complicated with AKI, and may take part in the appearance and growth of AKI. Similarly, Hu X M et al displayed that serum NGAL and KIM-1 extents were significantly grown in the death group, and the combined detection of the two tests had good predictive value for neonatal renal injury with sepsis at 28d.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Previous research on miR-320-3p has focused on pulmonary hypertension, ischaemia/reperfusion injury and muscle wasting in obesity. [10][11][12] In this study, the death group showed greatly higher the levels of serum miR-320-3p, NGAL, KIM-1 and the APACHE II mark than the survival group, suggesting that the levels of serum miR-320-3p, NGAL and KIM-1 are related to the severity of sepsis complicated with AKI, and may take part in the appearance and growth of AKI. Similarly, Hu X M et al displayed that serum NGAL and KIM-1 extents were significantly grown in the death group, and the combined detection of the two tests had good predictive value for neonatal renal injury with sepsis at 28d.…”
Section: Discussionmentioning
confidence: 63%
“…As far as we know, this is the first study which investigates miR‐320‐3p expression in AKI. Previous research on miR‐320‐3p has focused on pulmonary hypertension, ischaemia/reperfusion injury and muscle wasting in obesity 10–12 . In this study, the death group showed greatly higher the levels of serum miR‐320‐3p, NGAL, KIM‐1 and the APACHE II mark than the survival group, suggesting that the levels of serum miR‐320‐3p, NGAL and KIM‐1 are related to the severity of sepsis complicated with AKI, and may take part in the appearance and growth of AKI.…”
Section: Discussionmentioning
confidence: 64%
“…In the reported literature, in an experimentally induced ischemia/reperfusion model, higher miRNA‐320 levels were detected and reduced myocardial tissue damage was obtained by administration of miRNA‐320 anti‐miRNA‐320 45 . In another experimental study, it was shown that overexpression of miR‐320‐3p inhibited the protective pathways against ischemic injury on the myocardium 46 . Similarly, other ex vivo and in vivo studies demonstrated that miR‐320 has a regulatory role in ischemia reperfusion‐induced cardiac injury and dysfunction by the antithetical effect to heat‐shock protein 20 (Hsp20).…”
Section: Discussionmentioning
confidence: 96%
“…MiR-296-3p and miR-24-2-5p are important for embryonic stem (ES) cell (ESC) cardiac differentiation (Sun et al, 2011;Lee et al, 2016). MiR-320-3p can protect rat cardiomyocytes from ischemia/reperfusion (HR) injury through targeting Akt3 (Cao and Chai, 2020). MiR-30e-3p is involved in promoting cardiomyocyte autophagy and inhibiting apoptosis by regulating Egr-1 (Su et al, 2020).…”
Section: Discussionmentioning
confidence: 99%